PARTICIPATION OF EASTERN COUNTRIES IN FAIR TRADE (1920s) (American Journal of Business Management, Economics and Banking, 2023)
In this article, the participation of Eastern countries in Soviet trade fairs in the 20s of the last centuries, the activity of Central Asian economic agencies in this matter, i.e., the organization of an international trade fair in the region, and the position of central foreign trade organizations in relation to it are highlighted in the light of the historical materials of that time.